Analisis Indeks Nilai Relatif Produksi Perikanan Tangkap Kabupaten Tegal, Provinsi Jawa Tengah - Dian Sutono Hs; Noor Zuhry (Barakuda'45, 2022)
In the Tegal Regency area, there are two capture fisheries centers, namely Larangan Fish Auction Place in Munjungagung Village and Suradadi Fish Auction Place in Suradadi Village. This study aims to analyze the NP/P ratio and analysis of the Relative Production Value Index of capture fisheries products. The method used in this research is a case study method which is carried out on the marketing aspects of the caught fish landed at the Larangan Fish Auction Place and at the Suradadi Fish Auction Place, Tegal Regency. The calculation of the NP/P ratio and the Relative Production Value Index were carried out as the basis for analyzing the data. The results of the analysis showed that the Larangan Fish Auction Place in general experienced an increase, namely an average production growth of 15.30% and an average production value of 10.86%. Meanwhile, Suradadi Fish Auction Place experienced a decrease, namely the average production growth and production value were 5.71% and 6.09%, respectively. Calculation of NP/P Ratio and Relative Value Index of Capture Fisheries Production in Tegal Regency resulted in the Larangan Fish Auction Places NP/N Ratio is Rp. 8,843.60 and the average Production Value Relative Index is 1.17. While the Suradadi Fish Auction Place the average NP/N ratio is Rp. 4,637.34 and the average Production Value Relative Index is 0.62. The Larangan Fish Auction Place has a better marketing quality than the Tegal Regency level, while the Suradadi Fish Auction Place has a less good marketing quality than the Tegal Regency level.